11n+6=24

Simple and best practice solution for 11n+6=24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11n+6=24 equation:


Simplifying
11n + 6 = 24

Reorder the terms:
6 + 11n = 24

Solving
6 + 11n = 24

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 11n = 24 + -6

Combine like terms: 6 + -6 = 0
0 + 11n = 24 + -6
11n = 24 + -6

Combine like terms: 24 + -6 = 18
11n = 18

Divide each side by '11'.
n = 1.636363636

Simplifying
n = 1.636363636

See similar equations:

| -12+5x=-9 | | X/4-X/8=-7/8 | | 4n-4=8+7n | | -n-1/2=10 | | 0=18x+1 | | 2(4x-15)=3(x-15) | | 2x+10=5+3x | | 7a+16-3a=-44 | | 9+10a=10 | | (x-2)=3(x-3) | | (X)=2(1+3) | | 2(4x-15)=3(x+15) | | 3+3p=6 | | 4a+12=7 | | 4(x-9)=x-15 | | 4(y-8)=8 | | m/3-6 | | 8h^2-50= | | 4/9:134/72 | | 9+3y-2yt=14 | | x(2x+7)= | | 11-8b=-5-4b | | 4a+12=-16 | | 4(y-4)=2(y+25)-4 | | 10x-18=x+63 | | 5Y+9=8Y-6 | | -8+9n=10 | | 7m-6=-104 | | 7x+60=x+60 | | (4x^2+4x+1)-(4x^2+2)=8x+16 | | 3-(5x-1)/10=(x-1)/5-(x-3)/2 | | 5r=-1 |

Equations solver categories